Gamification as an Educational Method for Future HR Professionals - Bernik, Nejc; Šprajc, Polona (Sodobni pristopi v kadrovskem managementu in izobraževanju, 2026)
Gamification is becoming increasingly established in higher education as a method for fostering engagement and promoting active learning. It can also be applied in the education of future human resource (HR) professionals studying in the field of human resource management (HRM). Using the artificial intelligence tool ChatGPT, we developed an example of a gamified task that illustrates how higher-education educators can use simulations and models to present practical experiences to HRM students for future application in HR practice. In addition to this example, we also presented the kaleidoscope of effective gamification and the octalysis model for gamification and behaviour design, both of which are well-established frameworks that can enhance the effectiveness of HRM education. The paper highlights gamification as an approach for facilitating knowledge transfer in the mentoring and career-development processes of future HR professionals.